2017
DOI: 10.19044/esj.2017.v13n3p342
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Intelligence Techniques for Cancer Detection and Classification: Review Study

Abstract: Cancer is the general name for a group of more than 100 diseases. Although cancer includes different types of diseases, they all start because abnormal cells grow out of control. Without treatment, cancer can cause serious health problems and even loss of life. Early detection of cancer may reduce mortality and morbidity. This paper presents a review of the detection methods for lung, breast, and brain cancers. These methods used for diagnosis include artificial intelligence techniques, such as support vector … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 40 publications
1
9
0
1
Order By: Relevance
“…Regarding segments of AI in healthcare, the results of the present study revealed that the entire study sample was not aware of those segments. There was inconsistency with Al-shamasneh [3] and Erguzel [4] who stated that hospitals, either governmental or private healthcare centers and nursing homes are considered segments for AI use in healthcare. For example, in oncology AI can be used to aid doctors in the diagnosis and treatment of seven types of cancer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding segments of AI in healthcare, the results of the present study revealed that the entire study sample was not aware of those segments. There was inconsistency with Al-shamasneh [3] and Erguzel [4] who stated that hospitals, either governmental or private healthcare centers and nursing homes are considered segments for AI use in healthcare. For example, in oncology AI can be used to aid doctors in the diagnosis and treatment of seven types of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…There is a paradigm shift to digitalize healthcare sectors to get a competitive advantage in the labor market. [3,4] AI has managed to capture the attention of key healthcare stakeholders, who are now in a dilemma of whether or not to integrate it fully or partially in their businesses. [5,6] The name behind the idea of AI is John McCarthy, who began research on the subject in 1955 and assumed that each aspect of learning and other domains of intelligence could be described so precisely that they can be simulated by a machine.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical treatment driven by AI has the potential to make a significant difference in eliminating health inequities, especially in low-resource settings. AI integration in cancer care can increase diagnosis accuracy and speed, aid healthcare decision, and result in improved health outcomes (Al-shamasneh & Obaidellah, 2017). Artificial intelligence (AI) has the potential to improve cancer screening, tumor genetic characterization, drug discovery, and cancer surveillance.…”
Section: Ai Cancer Detection Solutionsmentioning
confidence: 99%
“…The expert system in health is not intended to replace the role of a doctor, but to help diagnose the patient's condition earlier [10]. Artificial Intelligence Techniques for Cancer Detection and Classification have been investigated [11]. Expert system as a tool to diagnose diseases with out of breath symptoms and also provide treatment solutions can be carried out through consultation by answering each a yes or no question [12].…”
Section: Introductionmentioning
confidence: 99%